PENGARUH FOOTCARE EDUCATION DAN SENAM KAKI TERHADAP RESIKO TERJADINYA ULKUS DIABETIK PADA PENDERITA DIABETES MELLITUS TIPE 2 DI WILAYAH KERJA PUSKESMAS ROGOTRUNAN LUMAJANG - Marchita, Ria Fitri; Hartono, Dodik; Abidin, Zainal (NHM PRESS, 2023)
Diabetes Mellitus (DM) needs serious attention both from patient and the health worker because DM increases the risk of complication such as cardiovascular disease and kidney failure. The symptoms’ that shown on the Diabetes Mellitus are polydipsia, polyuria, polyphagia, the slow wound healing, repeated infection, the decrease in vision, and fatigue. This research uses pre-experiment research with one group pretest-posttest design. This design used pretest before given treatment. There are 36 diabetes mellitus patient sampled for this research collected using purposive sampling technique. The data collection including coding, editing, entry, and cleaning, after that the data analyzed using SPSS. The research result shows that before the intervention of giving footcare education and foot exercise, the are 27 (75%) have low risk patients, 8 (22,8%) of medium risk patients, and 1 (2,8 %) of high risk patient with diabetic ulcer. After the intervention given, the respondents become 35 (97,2%) of low risk and only 1 (2,8%) of medium risk with diabetic ulcer. There is an effect of footcare education on the risk of developing diabetic ulcers in patients with type 2 diabetes mellitus at the Rogotrunan Lumajang Health Center with r = -3.000 so that r = 0.000 < α = 0.05. The result of this research is expected to be able to add and improve the knowledge of community to understand the importance of the treatment on the diabetic patient and foot exercise to improve the blood circulation so complication of diabetic ulcers can be prevented.